CHRM3 rs2165870 polymorphism is independently associated with postoperative nausea and vomiting, but combined prophylaxis is effective - Klenke, S.; de Vries, G.J.; Schiefer, L.; Seyffert, N.; Bachmann, H.S.; Peters, J.; Frey, U.H. (British journal of anaesthesia : BJA, 2018)
Clinical risk factors for postoperative nausea and vomiting (PONV) are evaluated with the Apfel score, however patients with low Apfel scores still experience PONV suggesting a genetic predisposition. PONV risk associates with specific M3 muscarinic acetylcholine receptor (CHRM3) rs 2165870 polymorphism. We investigated whether the Apfel score and this genetic variation independently contribute to PONV risk and whether prophylaxis reduces PONV in patients with low Apfel score but at high genetic risk. In a prospective, controlled study, 454 subjects undergoing elective surgery were genotyped for rs2165870 and its association with PONV was investigated with log-binomial regression analysis. Subjects were randomised to receive acustimulation/dexamethasone, acustimulation/vehicle, sham acustimulation/dexamethasone, or sham acustimulation/vehicle to investigate their effects on PONV risk. Early PONV occurred in 37% of subjects. The rs2165870 genotype distribution was GG in 191, GA in 207, and AA in 56 subjects. The CHRM3 polymorphism was associated with a relative risk (RR) of 1.5 for GA vs GG [95% confidence interval (CI): 1.1–1.9; P=0.003] and 1.6 for AA vs GG (95% CI: 1.1–2.2; P=0.009) genotypes to develop PONV, and this was independent from the Apfel score (RR per Apfel point: 1.3, 95% CI: 1.2–1.5; P<0.0001). While dexamethasone and acustimulation each reduced the PONV risk by 30% in AA genotype carriers with low Apfel score, combined therapy reduced the risk by 86% (P=0.015). The CHRM3 polymorphism and the Apfel score independently predict PONV susceptibility. Dexamethasone/acustimulation should be considered in patients with low Apfel score but at high genetic risk. DRKS00005664.